Tocilizumab in combination with corticosteroids: potential for managing cancer cachexia with systemic hyperinflammation - Chen, Ping; Wang, Dingyi; Zhan, Zhouwei; Chen, Ling; Chen, Yu (Frontiers in Immunology, 2024)
BackgroundCachexia is a leading cause of death among individuals with advanced cancer, yet effective pharmacological treatments are lacking. In this single-center retrospective study, we aimed to investigate the efficacy and safety of tocilizumab for the treatment of cancer cachexia accompanied by systemic hyperinflammation.MethodsData were collected from 20 patients treated with tocilizumab and a control group of 20 patients matched for age, sex, and comorbidities. Both groups received corticosteroids. In the tocilizumab treatment group, patients received a single dose of tocilizumab (8 mg/kg, maximum 800 mg) in combination with corticosteroids. Weight, body mass index, liver metastasis, Eastern Cooperative Oncology Group score, patient-generated subjective global assessments, the Anorexia/Cachexia Subscale of the Functional Assessment of Anorexia/Cachexia Therapy, handgrip strength, neutrophil-to-lymphocyte ratio, and the C-reactive protein, hemoglobin, prealbumin, and albumin levels were recorded in both groups.ResultsTocilizumab treatment favorably influenced the levels of patient biomarkers (p<0.05), ameliorated systemic inflammation, and demonstrated enhanced clinical short-term efficacy compared to the control group, including rates of symptomatic relief (60% vs. 20%, p = 0.024), improvement of serum PAB and ALB (70% vs. 25%, p = 0.004), weight gain >2% (45% vs. 15%, p = 0.038), and improvement of grip strength and 6-m walk speed (p<0.05). Treatment with tocilizumab was generally safe, with no observed increase in infection rates (10% vs. 15%, p = 0.633) or intensive care unit admissions (10% vs. 25%, p = 0.405), and was more favorable for restarting antitumor therapy (70% vs. 35%, p = 0.027).ConclusionsTocilizumab, in combination with corticosteroids, is favorable for alleviating cancer cachexia with systemic hyperinflammation, despite the small sample size. Thus, this combination holds great potential as a novel strategy for treating cancer cachexia with systemic hyperinflammation.